Publishing from the periphery: Structural heterogeneity and segmented circuits. The evaluation of scientific publications for tenure in Argentina's CONICET - Beigel, Maria Fernanda (2014)
Academic publishing is one of the most unequal areas of the circulation of ideas. Recent studies have analyzed the dominance of ISI-style standards and its consequences for scientific production in the periphery. This article delves into the Latin American publishing circuit and its performance in the midst of four different types of circuits in the world academic system: (a) mainstream ‘international’ publishing circuits, sustained by major private enterprises and publishing houses (Thomson Reuters, Elsevier, Google); (b) transnational networks and repositories built as open access (DOAJ, Dial-net, INASP) to create an alternative to previous (c) regional Southern circuits (LATINDEX, SCIELO, CLACSO, REDALYC, AJOL); and (d) national circuits based on local publications. Given that these four circuits all come into play in national scientific fields, this article addresses the case of Argentina in order to prove that these circuits are segmented, partly due to the hierarchies of the World Scientific System and partly to structural constraints and the local history of professionalization. Focusing on tenure evaluations for research positions at Argentina’s National Scientific Research Council (CONICET), the article examines the results of a survey among coordinators of the council’s evaluation committees in order to analyze the relationship between international publishing and tenure. By exploring the evaluative culture at CONICET, common trends are highlighted along with alternative forms of regional academic prestige